Masstransfer features in the apparatuses with a moving nozzle in a three-phase foam layer - Manoilo, Evgenia V.; Manoilo, Yuriy O.; Repko, Kalif Y.; Zhuha, Oleg O.; Davydov, Denis V.; Arslanaliiev, Tymur M. (Національний технічний університет "Харківський політехнічний інститут", 2024)
The improvement of heat and mass exchange equipment for sorption processes in the countercurrent contact of gas and liquid in combined block elements with a weighted spherical nozzle, as well as a more in-depth study of this process, is an urgent task of chemical technology. A fundamentally new type of ball-shaped three-dimensional mesh fluidized nozzle was developed and researched, the bodies of which are made of polymer layers with holes, and a freely coiled metal or polymer mesh is located inside. The nozzle has a high specific surface area, developed free volume and low bulk density. The study of mass transfer in the liquid and gas phases was carried out and the corresponding calculation equations were obtained. Dependencies for the calculation of the mass transfer coefficients and the efficiency of the combined block element on the mode and design parameters are established. The results of calculations based on the obtained dependencies show a sufficient correlation with the experimental data. The proposed model of the desorption process of carbon dioxide from water, which allows predicting the values of the efficiency indicators of the decarbonization process. It was established that the use of a combined block element with a ball-shaped nozzle allows to increase the mass transfer coefficients compared to the failure plate. The industrial implementation of absorption processes in the foam layer and the use of the gas-liquid layer stabilization method significantly expands the scope of application of foam apparatuses and opens up new opportunities for intensifying technological processes. Previously expressed assumption about the perspective of using mesh materials for the manufacture of nozzle bodies was confirmed by experiments, but the peculiarity of the operation of devices with similar nozzles should be emphasized.

Удосконалення тепломасообмінного обладнання для сорбційних процесів при протитечійному контакті газу і рідини в комбінованих блочних елементах з обважненою сферичною насадкою, а також більш поглиблене дослідження цього процесу є актуальним завданням хімічної технології. Розроблено та досліджено принципово новий тип кулястої тривимірної сітчастої псевдозрідженої насадки, корпуси якої виконані з шарів полімеру з отворами, а всередині розташована вільно навита металева або полімерна сітка. Насадка має високу питому поверхню, розвинений вільний об'єм і низьку насипну густину. Проведено дослідження масообміну в рідкій і газовій фазах та отримано відповідні розрахункові рівняння. Встановлено залежності для розрахунку коефіцієнтів масовіддачі та ефективності комбінованого блочного елемента від режимних і конструктивних параметрів. Результати розрахунків за отриманими залежностями показують достатню кореляцію з експериментальними даними. Запропонована модель процесу десорбції діоксиду вуглецю з води, яка дозволяє прогнозувати значення показників ефективності процесу декарбонізації. Встановлено, що використання комбінованого блочного елемента з кулеподібною насадкою дозволяє підвищити коефіцієнти масопередачі в порівнянні з провальною тарілкою. Промислова реалізація процесів абсорбції в пінному шарі та використання методу стабілізації газорідинного шару значно розширює сферу застосування пінних апаратів і відкриває нові можливості для інтенсифікації технологічних процесів. Раніше висловлене припущення про перспективність використання сітчастих матеріалів для виготовлення корпусів насадок підтвердилося експериментами, але слід підкреслити особливість роботи апаратів з подібними насадками.
Особливості масообміну в апаратах з рухомою насадкою в трифазному пінному шарі
Keywords: masstransfer; combined block element; three-phase interaction; perforated plate; turbulation; moving nozzle; decarbonization; масообмін; комбінований блок-елемент; трифазна взаємодія; перфорована тарілка; турбулізація; рухома насадка; декарбонізація